Sínodo diocesano: um serviço à missão da Igreja local - Bernardo, Bonifácio (2015)
Taking as a starting point the ecclesial experience of the diocesan Synods and the principal documents of the recent Magisterium on the subject, this text aims to make a brief retrospective and assessment on the Synods that have taken place in the different local Churches in Portugal following the 2nd Vatican Council, or are still in progress. The thread of this reflection may be glimpsed immediately from the title: the diocesan Synods are a precious service to the mission of the local Church that promotes them, to the extent that they contribute to projecting its renovation and its evangelising and missionary pastoral action. Communion, renovation, mission, evangelisation and joint responsibility are, among others, incisive words that make the diocesan Synods of this period pulsate with a rhythm.